Bloom : a novel - Couch, Robbie (Gallery Books, 2026)
Morris Warner is withering away. After the sudden death of his husband, Fred, he has shut himself off from the world. No more going to movies with friends, or swims in Lake Michigan, instead preferring the quiet loneliness of his history books and Jeopardy episodes with only the cat to hear his answers. Morris's stepdaughter, Sloan, feels like she has nowhere to grow. She's about to get married to the man of her dreams, if only her mother will let her actually plan her own wedding and trust her to build her own life after her father's death. Jade is drying out. Literally. As a plant in Morris's home, she and her plant housemates have been slowly wasting away, leaf by falling leaf, since Fred's death and Morris's lack of care. She needs to come up with a plan to make her new owner come back to life, no matter what it takes.